Notch maintains Drosophila type II neuroblasts by suppressing expression of the Fez transcription factor Earmuff - Li, Xiaosu (Development, 2016)
Notch signaling is crucial for maintaining neural stem cell (NSC) self-renewal and heterogeneity; however, the underlying mechanism is not well understood. In Drosophila, loss of Notch prematurely terminates the self-renewal of larval type II neuroblasts (NBs, the Drosophila NSCs) and transforms type II NBs into type I NBs. Here, we demonstrate that Notch maintains type II NBs by suppressing the activation of earmuff (erm) by Pointed P1 (PntP1). We show that loss of Notch or components of its canonical pathway leads to PntP1-dependent ectopic Erm expression in type II NBs. Knockdown of Erm significantly rescues the loss-of-Notch phenotypes, and misexpression of Erm phenocopies the loss of Notch. Ectopically expressed Erm promotes the transformation of type II NBs into type I NBs by inhibiting PntP1 function and expression in type II NBs. Our work not only elucidates a key mechanism of Notch-mediated maintenance of type II NB self-renewal and identity, but also reveals a novel function of Erm.